2017
DOI: 10.1038/nmicrobiol.2017.59
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the hexagonal surface layer on Caulobacter crescentus cells

Abstract: Many prokaryotic cells are encapsulated by a surface layer (S-layer) that consists of repeating units of S-layer proteins (SLPs). S-layers protect cells from the outside, provide mechanical stability, and also play roles in pathogenicity. In situ structural information on this highly abundant class of proteins is scarce, therefore atomic details of how S-layers are arranged on the surface of cells have remained elusive. Here, using purified C. crescentus’ sole SLP RsaA we obtained a 2.7 Å X-ray structure that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
147
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(165 citation statements)
references
References 52 publications
(57 reference statements)
10
147
1
Order By: Relevance
“…RsaA consists of two domains, both of which are necessary for successful S-layer assembly in vivo (Figure 1A) (10, 11). The N-terminal domain, here defined as RsaA 1-246 , is responsible for anchoring the protein to the cell surface via a non-covalent interaction with specific sugar moieties of the lipopolysaccharide (LPS) outer membrane (1113).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…RsaA consists of two domains, both of which are necessary for successful S-layer assembly in vivo (Figure 1A) (10, 11). The N-terminal domain, here defined as RsaA 1-246 , is responsible for anchoring the protein to the cell surface via a non-covalent interaction with specific sugar moieties of the lipopolysaccharide (LPS) outer membrane (1113).…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal domain, here defined as RsaA 1-246 , is responsible for anchoring the protein to the cell surface via a non-covalent interaction with specific sugar moieties of the lipopolysaccharide (LPS) outer membrane (1113). In contrast, the C-terminal region is responsible for making the inter-molecular contacts necessary to form the physiological S-layer lattice (10). A recent 2.7 Å resolution crystal structure revealed that the C-terminus, RsaA 249-1026 , consists of a series of beta-strands arranged in an L-shape and connected by loops interspersed with calcium-binding Repeat-in-Toxin (RTX) motifs (Figure 1A,B) (10, 14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, even though there are examples of bacterial species with S-layer that carry out peptidoglycan cellwall synthesis at mid cell (6), their new S-layer material is inserted as patches distributed all around the cell (35,36). Second, lack of conservation in the protein architecture between archaeal and bacterial S-layers argue that they may have emerged independently of each other (8,37).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple copies of the biological complex of interest can be identified within reconstructed tomograms, and 3D "subvolumes" can be extracted and averaged together in a process called subtomogram averaging (STA) [12][13][14][15][16][17][18][19][20] to obtain better resolved 3D reconstructions of the complex of interest. Notably, aspects of single-particle image processing have been incorporated into STA processing packages 18,19,21 , and combined with improved 3D-contrast transfer function (CTF) estimation and missing-wedge compensation 20,[22][23][24] to achieve reconstructions in the sub-nanometer resolution regime 9,20,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . Notably, high-resolution (3.9-3.1Å) reconstructions of the HIV-1 capsid-SPI region of the viral Gag protein has been determined using cryo-ET 20,23,40 , further emphasizing the promise of this technique in obtaining high-resolution structural information of complexes in situ.…”
Section: Introductionmentioning
confidence: 99%